Uji Kandungan Formalin dan Boraks pada sampel Ikan Asin - Taupik, Muhammad; Isa, Ishak; Ramadani Putri Papeo, Dizky; Kasim, Sesha Ramadhani (Universitas Negeri Gorontalo, 2024)
Salted fish is a well-known dish in Indonesia. Nationally, salted fish is one of the important fishery products, with almost 65% of fishery products being processed and preserved through salting. Formalin is a solution of 30- 50% formaldehyde gas (CH2O), commonly used for embalming, disinfecting, and as an antiseptic, as well as in plastics, antifreeze, paper, carpet, textile, construction materials, paint, and furniture industries. Borax is a chemical compound known as sodium tetraborate (Na2B4O7 10 Hâ‚‚O). Borax or boric acid is usually used in making detergents and antiseptics. The purpose of this research is to identify the presence of formalin and borax in salted fish and to determine the levels of formalin and borax in salted fish. This research employed qualitative analysis, using the permanganate, citric acid, and chromotropic acid methods for formalin detection. Turmeric paper, flame test, and AgNO3 precipitation methods were used for borax detection. Meanwhile, the quantitative analysis was conducted using the UV-Vis Spectrophotometry method. Based on the qualitative research results, all four samples tested negative for formalin, while one sample tested positive for borax. Consequently, the sample that tested positive for borax underwent quantitative analysis, revealing a borax level of 0,0975 g/kg in sample B.